(untitled) (Revista de Ciências Agroveterinárias, 2016)
Introduction of forage cultivars of different countries can be an option for technology short-term transfer for access to vegetative materials for better production potential. The objective of this study was to evaluate cultivars of temperate climate perennial grasses from Uruguay and New Zealand in soil and climatic conditions in Santa Catarina State, during the years 2010 to 2012. Two simultaneous experiments were conducted, in four physiographic regions of the State: West, Midwest, South Plateau and North Plateau. In trial 1 cultivars of Lolium perenne, festulolium and oats perennial and in trial 2 cultivars of Festuca arundinaceae and dactylis were evaluated. There was interaction between cultivars and localization in both trials, during the two years of evaluation. Perennial ryegrass and festulolium significantly reduced dry matter production (DMP) over the period in the West, Midwest and Northern Plateau and it is recommended only for South Plateau region. Perennial oats may be indicated for the two regions Plateau. In trial 2, the fescue cv. Epagri 312 (control) and cv. Aurora stood out in four locations, with average values of 9 and 7 t ha-1 of dry matter, respectively for the first and second periods of evaluation.